Multicenter 1‐month follow‐up study of the patch test reaction to the gold sodium thiosulfate of the TRUE Test and its association with piercings and dental metal history. (19th March 2021) - Suzuki, Kayoko; Matsunaga, Kayoko; Ito, Akiko; Yagami, Akiko; Ito, Takashi; Miyazawa, Hitoshi; Sugiura, Mariko; Adachi, Atsuko; Kubota, Yumiko; Watanabe, Yuko; Kato, Atsuko; Nishioka, Kazue; et al.
Abstract: Background: There is controversy over late and long‐lasting reactions to gold sodium thiosulfate (GST). Objectives: To study the GST patch test reaction by observing the application site after 1 month, and to clarify the relevance of GST sensitization by piercings and dental metals. Patients: A retrospective analysis was performed on 746 patients (143 male; 603 female) who were patch tested using GST of the TRUE Test. We conducted a questionnaire on the presence of piercings or dental metals in these patients. Results: The GST positive rate was 27.9% at day (D)3 and/or D7 and 40.3% up to the 1‐month reading. The positive rate was significantly higher in female patients and increased with age. Sixty‐two percent of cases with a positive reaction at D7 continued to show a positive reaction after 1 month. Eleven percent of cases with a negative reaction at D3 and D7 showed a late reaction. Both piercings and dental metals were related to gold sensitization. Conclusions: The GST of the TRUE Test had a high positive and low false‐negative rate. The 1‐month reading after the patch test was important for identifying late reactions. Piercing history and dental metal were associated with gold sensitization.